2019
DOI: 10.1080/14693062.2019.1704678
|View full text |Cite
|
Sign up to set email alerts
|

Loss and damage in the IPCC Fifth Assessment Report (Working Group II): a text-mining analysis

Abstract: Losses and damages' refer to impacts of climate change that have not been, or cannot be, avoided through mitigation and adaptation efforts. After the establishment of the Warsaw International Mechanism for Loss and Damage (WIM), Loss and Damage is now considered the third pillarbesides mitigation and adaptationof climate action under the United Nations Framework Convention on Climate Change (UNFCCC). This paper studies what the Contribution of Working Group II to the Fifth Assessment Report of the Intergovernm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The latter is unlikely given failures of governance around negative emissions technologies [76][77][78] . As such, a longer-term post-2100 perspective is critical for assessing the scope of climate change on Earth systems and human well being 79 .…”
Section: Governance and Research For Long Timescalesmentioning
confidence: 99%
“…The latter is unlikely given failures of governance around negative emissions technologies [76][77][78] . As such, a longer-term post-2100 perspective is critical for assessing the scope of climate change on Earth systems and human well being 79 .…”
Section: Governance and Research For Long Timescalesmentioning
confidence: 99%
“…Recent IPCC reports have shown that the impacts of climate change can already be observed on natural and human systems (IPCC 2018(IPCC , 2019van der Geest and Warner 2020). Rising temperatures, changing precipitation patterns and increased frequency of extreme weather events due to climate change are adversely affecting food and livelihood security and leading to land degradation and increased displacement (Zommers et al 2016;IPCC 2018IPCC , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of climate change on the human environment has increased progressively and extensively (Seo et al, 2013; Ju et al, 2013; Calzadilla et al, 2013; Noufé et al, 2015), and since the First World Climate Conference in 1979, climate change research has gradually attracted global attention (Iglesias, 2012; Ahmad et al, 2019; Mayank et al, 2019; Pons et al, 2020). The World Meteorological Organization (WMO) and the United Nations Environment Programme (UNEP) are two major organizations dealing with climate change, that simultaneously established the Intergovernmental Panel on Climate Change (IPCC) (Van der and Warner, 2020). The various assessment reports put forward by the IPCC since 1990 have established a scientific basis for climate change research, by indicating that global warming was caused by both natural and manmade factors.…”
Section: Introducionmentioning
confidence: 99%